Investigating cooling performance and energy utilization of refrigerated shipping container packed with fresh Fruit using computational fluid dynamics modelling - Getahun, Samuel Tenaw (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.